Broilers Litter Management: A Review of Environmental Impacts, Nutritional Value and Sustainable Utilization - Niran, Ayanniyi (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
The continuous demand for animal protein occasioned by increase in population has placed much pressure on researchers across the world for improved ways towards increasing animal productivity. The situation is unpalatable as efforts in meeting the needs have been met with insecurity, unregulated policy, natural disasters, unnecessary community conflicts, and problems of land grabbers most especially in developing nations. This has therefore necessitated at different fora exploration of alternative feed resources to increase animal’s productivity and arrest the ugly trernd. Broilers litter, which include poultry droppings, feed waste and also bedding materials has been identified as possible feed resource technology for the ruminant animals’ production. They have high quality nutritional value and can be manipulated and improved upon for higher animal yield. The use of the litter in ruminants business has become an increasingly popular area in ruminant animal agriculture. Although there are associated concerns for safety of meat and milk products from animals managed on such diets despite its high energy contents. Incidentally, information of its inclusion in the diets of ruminant animal agriculture has not been adequately documented. This therefore forms the basis for this work putting into consideration the consequential effects of broiler litters on animal health, its processing, sustainability, safety and its relative implication for the good of man and his environment. Keywords: Feed shortage, non-conventional feeds, poultry litter, environment